Genotypic determination coefficient and estimation of other parameters in rubber tree clones - Gonçalves, Paulo de Souza; Rossetti, Adroaldo G.; Valois, Afonso Celso C.; Viegas, Ismael de Jesus M. (Pesquisa Agropecuaria Brasileira, 2014)
Estimates of genetic variability were obtained for a fixed set of fourteen clones of rubber tree, Hevea spp. The set comprised clones from Fx, IAN and PFB series, all selected in the Northern region of Brazil. The characters studied were yield of dry rubber per tapping by Mendes early test, height, stem diameter, whorls number, leaf thickness, bark thickness, total number of latex vessel rings, diameter of latex vessels, density of latex vessels per 5 mm of ring, and average distance of consecutive latex vessel rings. The genotypic coefficient of variation ranged from 1.06% to 59.15%. The genotypic coefficient of determination estimates were 0.96, 0.79, 0.77 and 0.69 for yield, whorls number, stem diameter and bark thickness, respectively. The estimated genetic gain was low for total number of latex vessel rings and diameter of latex vessels and, hence, selection for these characters may not result in accentuated progress. Selection of clones based on yield, stem diameter and average distance between consecutive latex vessel ring a may be effective.